Catholic Renewal of the Classical Liberal Arts - Giancarlo Vera (Educationis Momentum)
The classical liberal arts are an educational model that had a tremendous influence on education for centuries. The early Christians superimposed their religious formation on this traditional academic course, and, eventually, the Catholic understanding of the human person and the world transformed the approach to classical education, elevating the aspirations of the model. This paper aims at researching this transformation, going deeper into how two important principles of Catholic education renew the classical liberal arts: Catholic anthropology and the unity of knowledge within the Catholic worldview.